2008
DOI: 10.1590/s1413-86702008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance patterns of pediatric community-acquired urinary infections

Abstract: Knowledge about antimicrobial resistance patterns of the etiological agents of urinary tract infections (UTIs) is essential for appropriate therapy. Urinary isolates from symptomatic UTI cases attended at Santa Casa University Hospital of São Paulo from August 1986 to December 1989 and August 2004 to December 2005 were identified by conventional methods. Antimicrobial resistance testing was performed by Kirby Bauer's disc diffusion method. Among the 257 children, E. coli was found in 77%. A high prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
32
1
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 11 publications
14
32
1
8
Order By: Relevance
“…The results showed a considerable increase in resistivity of gram negative isolates to amoxycillin (80.36%) which was supported by several studies 11,12,18 . Nitrofurantoin demonstrated better activity against gram negative (98.21% susceptible) as well as gram positive isolates (100.0% susceptible), in agreement with data published by others 17,18,19 . The high level susceptibility of uropathogens to nitrofurantoin may be the narrow spectrum of activity, narrow tissue distribution (low or undetectable serum concentration) and limited contact with bacteria outside the urinary tract 20 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed a considerable increase in resistivity of gram negative isolates to amoxycillin (80.36%) which was supported by several studies 11,12,18 . Nitrofurantoin demonstrated better activity against gram negative (98.21% susceptible) as well as gram positive isolates (100.0% susceptible), in agreement with data published by others 17,18,19 . The high level susceptibility of uropathogens to nitrofurantoin may be the narrow spectrum of activity, narrow tissue distribution (low or undetectable serum concentration) and limited contact with bacteria outside the urinary tract 20 .…”
Section: Discussionsupporting
confidence: 90%
“…Cotrimoxazole was replaced by fl uroquinolones and cephalosporins because of high level of resistance to this drug but unfortunately after sometime resistance to these drugs was also detected and published. Our study also showed the similar fi ndings with 28.5-30.35% resistance to quinolones, 39.2-50.0% resistance to cephalosporins and 48.21% resistance to cotrimoxazole for gram negative isolates 17 . The results showed a considerable increase in resistivity of gram negative isolates to amoxycillin (80.36%) which was supported by several studies 11,12,18 .…”
Section: Discussionsupporting
confidence: 85%
“…coli resistance to cotrimoxazole in most developing countries demonstrated similar results. For example, this resistance has been reported 68.1% in Senegal (46), 58% in Turkey (98), 53% in Lebanon (102), 55% in Brazil (103), and 60% in Mexico (104). E. coli in Bangladesh showed the lowest susceptibility (20 -27%) to cotrimoxazole (105).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infection ranks one of most common medical disease encountered in medical practice with significant morbidity and health costs, occurring from neonate to elderly [11,12].…”
Section: Discussionmentioning
confidence: 99%